Inhibition of the TRPM2 and TRPV1 Channels through Hypericum perforatum in Sciatic Nerve Injury-induced Rats Demonstrates their Key Role in Apoptosis and Mitochondrial Oxidative Stress of Sciatic Nerve and Dorsal Root Ganglion - Uslusoy, Fuat; Nazıroğlu, Mustafa; Çiğ, Bilal (Frontiers in Physiology, 2017)
Sciatic nerve injury (SNI) results in neuropathic pain, which is characterized by the excessive Ca2+ entry, reactive oxygen species (ROS) and apoptosis processes although involvement of antioxidant Hypericum perforatum (HP) through TRPM2 and TRPV1 activation has not been clarified on the processes in SNI-induced rat, yet. We investigated the protective property of HP on the processes in the sciatic nerve and dorsal root ganglion neuron (DRGN) of SNI-induced rats. The rats were divided into five groups as control, sham, sham+HP, SNI and SNI+HP. The HP groups received 30 mg/kg HP for 4 weeks after SNI induction. TRPM2 and TRPV1 channels were activated in the neurons activated by ADP-ribose or cumene peroxide and capsaicin, respectively. The SNI-induced TRPM2 and TRPV1 currents and intracellular free Ca2+ and ROS concentrations were reduced by HP, N-(p-amylcinnamoyl) anthranilic acid (ACA) and capsazepine (CapZ). SNI-induced increase in apoptosis and mitochondrial depolarization in sciatic nerve and DRGN of SNI group were decreased by HP, ACA and CapZ treatments. PARP-1, caspase 3 and 9 expressions in the sciatic nerve, DRGN, skin and musculus piriformis of SNI group were also attenuated by HP treatment. In conclusion, increase of mitochondrial ROS, apoptosis and Ca2+ entry through inhibition of TRPM2 and TRPV1 in the sciatic nerve and DRGN neurons were decreased by HP treatment. The results may be relevant to the etiology and treatment of SNI by HP.